Side Effects of Steroidal And Non-Steroidal Anti-Inflammatory Drugs on The Oral Cavity. - Shayma Ghazi (Erbil Dental Journal, 2024)
Background and objectives: The steroidal and Non-Steroidal Anti-Inflammatory drugs (NSAIDs) are widely used classes of medications for their anti-Inflammatory and analgesic effects and are associated with the risk of many oral side effects and which might be presented with variable degrees of severity. The main objective of this research was to identify oral side effects that could be associated with using Steroidal or NSAIDs.